1978
DOI: 10.1128/jb.134.3.1157-1170.1978
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bacillus cereus temperature-sensitive mutants altered in spore coat formation

Abstract: Three conditional Bacillus cereus mutants altered in the assembly or formation of spore coat layers were analyzed. They all grew as well as the wild type in an enriched or minimal medium but produced lysozyme and octanol-sensitive spores at the nonpermissive temperature (35 to 38°C). The spores also germinated slowly when produced at 350C. Temperature-shift experiments indicated that the defective protein or regulatory signal is expressed at the time of formation of the outer spore coat layers. Revertants rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Wilson and Benoit (1993) and Benoit et al (1995) reported similar observation on the effect of LAA on Btk germination. While many findings reported that coatless spores have decreased rate of germination (Nakatani et al, 1985a;1985b -Bacillus megaterium) or at a rate that comparable to coated spores (Stelma et al, 1978;Kutima and Foegeding, 1987 -Bacillus cereus), the current study showed opposite trend, where rate of germination was increased by removal of spore coat. These results made the influence of coat on germination remain unclear however it may be related to species.…”
Section: Discussioncontrasting
confidence: 72%
“…Wilson and Benoit (1993) and Benoit et al (1995) reported similar observation on the effect of LAA on Btk germination. While many findings reported that coatless spores have decreased rate of germination (Nakatani et al, 1985a;1985b -Bacillus megaterium) or at a rate that comparable to coated spores (Stelma et al, 1978;Kutima and Foegeding, 1987 -Bacillus cereus), the current study showed opposite trend, where rate of germination was increased by removal of spore coat. These results made the influence of coat on germination remain unclear however it may be related to species.…”
Section: Discussioncontrasting
confidence: 72%
“…Such spores can be germinated artificially by addition of cortex-lytic enzymes, such as lysozyme, or spore-specific enzymes (1,4,27). Coatless spores have been observed to germinate at a decreased rate (13,17,18,28), and in somne cases mutants lacking spore coats germinate at a rate comparable to normal spores (26). The exact involvement of the coat and outer membrane in germination is unclear.…”
mentioning
confidence: 99%
“…A number of previous reports have suggested that spore-coat proteins may be synthesized as highmolecular-weight precursors, which are proteolytically cleaved to produce smaller mature proteins (Cheng & Aronson, 1977;Aronson & Pandey, 1978;Munoz et al, 1978a,b;Stelma et al, 1978;Pandey & Aronson, 1979;Aronson, 1981;Goldman & Tipper, 1981). These precursors can be identified immunologically in both Bacillus cereus and Bacillus subtilis as proteins ranging from mol.wt.…”
mentioning
confidence: 99%